2021
DOI: 10.3389/fphar.2021.790108
|View full text |Cite
|
Sign up to set email alerts
|

Causality Evaluation of Drug-Induced Liver Injury in Newborns and Children in the Intensive Care Unit Using the Updated Roussel Uclaf Causality Assessment Method

Abstract: Purpose: Drug-induced liver injury (DILI) is a common adverse reaction in the clinic; however, there are relatively few reports of DILI in critically ill newborns and children. Making use of the Pediatric Intensive Care database (PIC), this study identifies which drugs are related to DILI in neonates and children in China.Methods: Using the PIC, we screened for patients whose liver was suspected of being injured by drugs during hospitalization. The medicine they used was then assessed by the Roussel Uclaf Caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Additionally, the present study is the first to report that tac-DILI tends to occur at a younger age. Drug use is recognized as a cause of pediatric liver disease, but little is known about DILI in children and adolescents ( Ferrajolo et al, 2010 ; Ye et al, 2021 ). Age distribution analysis showed that 15.2% and 53.3% of non-tac-DILI and patients with tac-DILI, respectively, were ≤18 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the present study is the first to report that tac-DILI tends to occur at a younger age. Drug use is recognized as a cause of pediatric liver disease, but little is known about DILI in children and adolescents ( Ferrajolo et al, 2010 ; Ye et al, 2021 ). Age distribution analysis showed that 15.2% and 53.3% of non-tac-DILI and patients with tac-DILI, respectively, were ≤18 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The top drugs causing RUCAM-based DILI worldwide have been assessed as to whether they were metabolized through CYP isoforms [62]. Literature provided highquality data on clinical features of DILI [1][2][3][4][5][6][7][8][9][10][16][17][18][19][20][21][22][23][24][25][26][27][28]39,64]. However, although most of the clinical features are well established, a variety of mechanistic steps remain unresolved in this complex disease.…”
Section: Basics Of Molecular and Mechanistic Toxicology In Dilimentioning
confidence: 99%
“…Cessation of all non-essential drugs is mandatory as soon as the idiosyncratic DILI is suspected [13,28,29,90,91]. This alone has a positive effect on LTs as shown in many reports on DILI with verified diagnosis based on the RUCAM [1][2][3][4][5][6][7][8][9]. In most cases, a complete resolution of the liver injury is achieved, while in a few others, a protracted course of LTs is observed.…”
Section: Initial Therapy Of Dili By Drug Cessationmentioning
confidence: 99%
See 1 more Smart Citation
“…The updated Roussel Uclaf Causality Assessment Method (RUCAM) is an algorithmic diagnostic method for DILI (Table 1) (9,10). The RUCAM was created for adults, but it has been used successfully in children in the DILIN prospective study, the Latin American DILI Registry, the Spanish DILI registry and in 2 pediatric retrospective studies (16)(17)(18)(19). It is based on liver test thresholds, liver injury pattern, timing of events, risk factors, comedications, known hepatotoxicity of the drug, response to re-exposure, and most importantly, exclusion of alternative causes (ruling out infections, ischemia, gallbladder disease and autoimmune hepatitis, among others).…”
Section: Diagnosismentioning
confidence: 99%